Law No. 185 of the Year 2023 Amending Certain Provisions of the Penal Code = قانون رقم 185 لسنة 2023 بتعديل بعض أحكام قانون العقوبات - The Middle East Library for Economic Services (The Middle East Library for Economic Services, 2025)
English & Arabic